URGENSI HAK ANGKET, PEMAKZULAN PRESIDEN DALAM SISTIM KETATANEGARAAN INDONESIA - Hadi Karyono; Mahmudah Pancawisma; Benny Bambang Irawan (Hukum dan Dinamika Masyarakat, 2024)
In the Indonesian constitutional system, the House of Representatives is given legislative, budgetary and supervisory functions. In carrying out its functions, the House of Representatives is given the right of interpellation, the right of inquiry and the right to express opinions as regulated in the law and other statutory regulations. Impeachment of the President or what is known as the removal of the President in the constitutional system is regulated in the 1945 Constitution of the Republic of Indonesia articles 7A and 7B. In article 7A it is stated that "the President and/or Vice President can be dismissed during their term of office by the People's Consultative Assembly at the suggestion of the House of Representatives, whether they are proven to have committed a violation of the law in the form of treason against the state, corruption, bribery, other serious criminal acts, or disgraceful acts. or if it is proven that he no longer meets the requirements as President and/or Vice President." The problem is that recently there has been a heated debate about the right to inquiry, the aim of which is to impeach the President for alleged violations in the 2024 general election. What is the legal regulation regarding the right to inquiry? Can the right of inquiry regarding the implementation of elections carried out by the KPU be assigned to the President? Can the right of inquiry be a basis for removing the President from office? This type of research is a normative legal research type. The approach used is the legislative and comparative legal approach (comparison approach), the legal philosophy approach (philosophical approach). The results of the research show that the right to inquiry is the right of the House of Representatives to conduct investigations into the implementation of a law and/or government policy relating to important, strategic matters and having a broad impact on the life of society, nation and state which is suspected to be in conflict with statutory regulations. -invitation. Based on the original intent of the right to inquiry norm in the comprehensive text of the amendments to the Constitution, the right to inquiry is only intended for state institutions in the executive family. The KPU as an independent institution as an election organizer can carry out a questionnaire, whereas the decision on the right to a questionnaire is a political decision, its recommendation cannot automatically impeach the President, to be able to impeach there is of course a follow-up process for allegations that the President has violated the laws and regulations as stipulated in article 7 A Constitution of the Republic of Indonesia of 1945.